Effects of nobiletin on PhIP-induced prostate and colon carcinogenesis in F344 rats - Tang M. (2017)
The current study was designed to investigate the effects of nobiletin (5,6,7,8,3′,4′-hexamethoxy flavone) on 2-amino-1-methyl-6- phenylimidazo[4,5-b]pyridine (PhIP)-induced prostate and colon carcinogenesis. PhIP was administered to 6-wk-old F344 male rats intragastrically (100 mg/kg) twice a wk for 10 wk. The animals were given 0.05% nobiletin or the basal diet for 50 wk. At the end of the experiment, serum testosterone, estrogen, and leptin did not differ between the 2 groups. The body weights of nobiletin-treated rats were significantly higher than controls (P < 0.05), and feeding of nobiletin significantly reduced the relative prostate (P < 0.05) and testes (P < 0.05) weights as well as the Ki67 labeling index in the normal epithelium in the ventral prostate (P < 0.01). The incidence and multiplicity of adenocarcinomas in nobiletin-treated ventral prostate were 50% and 36%, respectively, of controls, but the differences were not statistically significant. However, nobiletin did significantly reduce the total number of colonic aberrant crypt foci (ACF) compared to the control value (P < 0.05). Nobiletin, therefore, may have potential for chemoprevention of early changes associated with carcinogenesis in both the prostate and colon. Copyright © 2011, Taylor & Francis Group, LLC.